Potato starch, an alternative gelling agent in culture media for in-vitro propagation of lulo Solanum quitoense L - G., Darío Martín; Cárdenas, Oswaldo; Cárdenas, Agobardo (Revista de Ciencias Agrícolas, 2013)
Plant tissue culture is a widely technique used in propagation, being a disadvantage the high cost of the culture media used specially that of the agar, that represents a high percentage of costs. In this work, we evaluated the partial replacement of agar for potato starch of Diacol Capiro variety, in proportions of 50, 45 and 40% in culture media for lulo micropropagation Solatium quitoense Lam. It was observed a decrease of media consistency with an increment of potato starch. Statistical significance was found in the length of the explants, getting the best result with a gelled mix of 60-40 (agar-potato starch); other variables analized were not statistically significant.Finally it is concluded that potato starch can be a potential substitute as a gelling agent for vegetative propagation of lulo in media cultures.